Consumption populism: how business leaders use populist logic to shape consumption - Shafiullah Anis (Journal of business ethics, 2026)
The populist turn in politics has inspired extensive scholarship across disciplines; however, the role of populist business leaders remains under-theorized. This article addresses this gap by introducing the concept of consumption populism. Drawing on Ernesto Laclau’s conceptualization of populism, we examine the case of Baba Ramdev—a far-right Hindu-nationalist yoga guru turned businessman in India—who promotes neo-Swadeshi consumption populism. Our contribution lies in conceptualizing a non-essentialist understanding of consumption populism as a process of constructing "the people" without any predefined essence. This is underscored through the application of the discursive-hegemonic model of market constitution. A key contribution of this study is the development of a three-stage process model for consumption populism, illustrating how business leaders articulate and practice it through three interrelated logics: otherization, homogenization, and hegemony. These logics are enacted via three distinct practices: mobilizing affect, creating spectacles, and posing impossible demands. Additionally, we explore the critical role of affect in constructing collective populist identity. The article also examines the ethical implications of exclusionary consumption populism on vulnerable consumers, interrogates the role of neo-liberal business elites in perpetuating these dynamics, and considers the possibilities of a non-exclusionary form of consumption populism where antagonism is replaced with an agonistic logic.